Studi Pengaruh Temperatur Kondensasi Terhadap Kinerja Siklus Rankine Organik Menggunakan Fluida Kerja R245FA Dan R515A - Lobo, Jefrianto; Dwinanto, Matheus M.; Nurhayati, Nurhayati (Universitas Nusa Cendana, 2022)
Since 2000 power plants with the organic Rankine cycle (ORC) are the most widely used in the world that utilize low-temperature heat sources such as industrial heat waste, biomass, geothermal and solar energy. The working fluid for the ORC system must meet several criteria of physical properties including, environmentally friendly, non-flammable, non-toxic, and non-corrosive. Therefore, this study aims to analyze the effect of condensation temperature on the thermodynamic performance of a standard organic Rankine cycle with turbine power of 20 kW with working fluids R245FA, and R515A. Simulation of system performance using Genetron Properties software with evaporation temperature held constant at 80oC and condensation temperature varied at 30 – 40oC. The results of this study indicate that increasing the condensing temperature greatly increases the pumping power consumption but decreases the pressure ratio in the turbine, and the thermal efficiency of the system. The pumping power used to circulate the R515A is ±2.2 times higher than that of circulating it. The thermal efficiency of the ORC system that uses the two working fluids reviewed does not have a significant difference